Hourly irradiance data measured underwater on oyster tables during a one-year semi-controlled experiment - Damien Tran; Audrey Botté; Yannick Geerebaert; Laura Payton (PANGAEA, 2025)
This dataset shows the hourly irradiance data measured underwater on each oyster table (control and ALAN conditions, at the oysters extquotesingle level) throughout the year of the experiment as well as the temperature recorded by each irradiance sensor.
In: Tran, D et al. (2025): Valve behavior of the oysters Crassostrea gigas and Ostrea edulis and physicochemical data measured during a one-year semi-controlled experiment testing the in situ impact of artificial light at night [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.983250